Systematic Literatur Review : Evaluasi Kebijakan Program Rehabilitasi Rumah Tidak Layak Huni (RTLH) Bagi Masyarakat Berpenghasilan Rendah di Indonesia (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The Uninhabitable House Rehabilitation Program (RTLH) is a government policy aimed at improving the quality of housing for low-income communities while simultaneously supporting the acceleration of the eradication of extreme poverty. Although it has been implemented in various regions, the implementation of the RTLH program has shown varying achievements, thus requiring a comprehensive evaluation. This study aims to analyze the evaluation of the RTLH Program in Indonesia based on William N. Dunn's six policy evaluation indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The research method used is a Systematic Literature Review (SLR) of scientific articles discussing the evaluation of the RTLH Program in various regions. The analysis was conducted by reviewing previous research findings based on the six policy evaluation indicators. The results of the study indicate that the RTLH Program is able to improve the quality of community housing and has received a positive response from beneficiaries. However, its implementation still faces obstacles such as budget limitations, equal distribution of beneficiaries, and data updates. Therefore, strengthening funding, data collection, and coordination between stakeholders is needed for more optimal and sustainable program implementation.